The Extent of Job Satisfaction among PNP Personnel at Gen. Trias Component City Police Station - Asido Jr, Zosimo; Bantiyag, Larry M.; Lacaste Jr., Hilario; Picardal, Jr, Teodoro M.; Postrero, Christopher M.; Villa, Elizabeth; Mobo, Froilan D.; Golla, Nathaniel S. (Future Science / FSH-PH Publications, 2025)
The study sought to evaluate the level of job satisfaction among PNP personnel at the Gen. Trias Police Station, as assessed by the PNCOs and PCOs concerning Organizational Factors, Environmen-tal Factors, and Personal Factors. This study employed a quantita-tive-descriptive methodology. This research utilized a survey methodology for data collection. The research strategy employed stratified sampling to catego-rize a population into strata based on a known feature for each sampling unit, followed by the independent selection of samples from each stratum. The majority of respondents comprised forty-four (44) Police Non-Commissioned Officers and four (4) Police Commissioned Officers, indicating a predominance of male partic-ipation in this study. The study's ultimate outcome is a proposed action plan to im-prove job satisfaction among PNP personnel in Gen. Trias, Compo-nent City Police Station, as detailed in Sub-problem No. 4. The re-sults underscored the importance of organizational variables in-side the PNP organization. PNP personnel are influenced by their job environment and atmosphere. The data imply that sustaining open communication promotes greater outcomes.